1983
DOI: 10.1111/j.1445-5994.1983.tb02614.x
|View full text |Cite
|
Sign up to set email alerts
|

A Simple Aid to the Differential Diagnosis of Oliguria

Abstract: A study was conducted in oliguric and acutely azotemic patients, measuring: (i) the fractional excretion of sodium (FENa) using creatinine clearance as a measure of glomerular filtration rate, and (ii) sodium clearance relative to urea clearance, designated as the sodium/urea clearance ratio (Na:urea CR). It was found that FENa discriminated between "tubular" and "non-tubular" disorders in 96% of patients. Further, Na:urea CR was as discriminating as FENa. Patients with Na:urea CR above 2.5% can be reliably di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

1989
1989
2022
2022

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 7 publications
0
4
0
Order By: Relevance
“…Although the FENa test should be done early in the disease before the final diagnosis, six studies (21,23,26,29,39,40) were unclear if the index test was interpreted separately from the reference standard. In five (9,21,23,26,29) of the included studies, we were uncertain whether the interval between the index test and the reference standard was appropriate. Finally, most of the studies' patients were hospitalized, which may affect the external validity of our findings.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although the FENa test should be done early in the disease before the final diagnosis, six studies (21,23,26,29,39,40) were unclear if the index test was interpreted separately from the reference standard. In five (9,21,23,26,29) of the included studies, we were uncertain whether the interval between the index test and the reference standard was appropriate. Finally, most of the studies' patients were hospitalized, which may affect the external validity of our findings.…”
Section: Discussionmentioning
confidence: 99%
“…All of the studies used the clinical responsiveness to fluids as a reference standard, and two of them included patients with HRS and AKI (19,24,25). Additionally, four studies (6,7,21,26) used histopathologic examination other than response to fluid expansion, whereas nine studies (4,9,20,(22)(23)(24)(27)(28)(29)(30) supported their findings using microscopic urine analysis.…”
Section: Study Selection and General Informationmentioning
confidence: 99%
“…We failed to confirm the presence of pathological changes compatible with ATIN; however, we believe that the administration of loxoprofen sodium contributed, at least in part, to the development of the renal manifestations observed in the current patient. Indeed, the fact that our patient had an FENa level below 1% just after admission suggests the presence of reduced glomerular perfusion, presumably due to a decrease in vasodilators, including vasoactive prostaglandins and chemotactic leukotrienes, induced by loxoprofen sodium (4,23,26). Such mechanisms might also be implicated not only in the functional and ultrastructural alterations of the glomeruli that induce increases in glomerular protein permeability compatible with minimal change nephrotic syndrome, but also in the renal ischemia caused by severe renal vasoconstriction that would be accelerated by the presence of concomitant atherosclerotic lesions and/or arteriolar nephrosclerotic changes, thus resulting in the AKI associated with acute tubular injuries (23,25).…”
Section: Discussionmentioning
confidence: 99%
“…Multiple subsequent studies also showed a good value for FENa in differentiating prerenal AKI from ATN. 3 5 The abovementioned studies, however, did not include patients with CKD or patients on diuretics. In addition, some reports found that FENa <1% can be seen in states other than prerenal AKI (such as pigment nephropathy) and >1% can be seen in states other than ATN (such as with diuretic use).…”
mentioning
confidence: 99%